2020
DOI: 10.1017/s0142716420000272
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the relationship between working memory and second language reading comprehension: Does task type matter?

Abstract: Despite the increasing attention paid to the role of working memory in reading, findings and measurement of working memory have been inconsistent. The current meta-analysis aims to provide a quantitative description of the overall relationship between second language (L2) reading comprehension and working memory measured through reading span task and identify methodological features that moderate this relationship. Following a comprehensive search, 25 primary studies (23 peer-reviewed studies and 2 dissertatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 65 publications
7
24
1
Order By: Relevance
“…Between L1-and L2-based WM tasks, various correlations have been reported (e.g., r = .72 and .84, Osaka & Osaka, 1992; r = .39, Harrington & Sawyer, 1992). For the WM-L2 reading relationship, Linck et al (2014) showed no moderating effect across L1 and L2 (r = .228 and .229), whereas Shin (2020) reported that the relationship was stronger in L2 WM tasks (r = .35) than in L1 WM tasks (r = .17). Therefore, it remains unclear whether and to what extent stimulus language moderates the WM-L2 reading relationship.…”
Section: Working Memory Task Languagementioning
confidence: 99%
See 3 more Smart Citations
“…Between L1-and L2-based WM tasks, various correlations have been reported (e.g., r = .72 and .84, Osaka & Osaka, 1992; r = .39, Harrington & Sawyer, 1992). For the WM-L2 reading relationship, Linck et al (2014) showed no moderating effect across L1 and L2 (r = .228 and .229), whereas Shin (2020) reported that the relationship was stronger in L2 WM tasks (r = .35) than in L1 WM tasks (r = .17). Therefore, it remains unclear whether and to what extent stimulus language moderates the WM-L2 reading relationship.…”
Section: Working Memory Task Languagementioning
confidence: 99%
“…They investigated whether these relationships were moderated by variables such as participant characteristics and WM measurement features, concluding that WM capacity has a robust positive relationship with L2 proficiency. Shin (2020) focused on reading span tasks and meta-analyzed correlations between discourse-level L2 reading and WM. A small relationship was found between L2 reading comprehension and WM ( r = .30 [.24, .35], 25 studies).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, a growing amount of empirical research suggests that there is a positive relationship between working memory capacity and L2 outcomes. Results of several narrative reviews (Jackson, 2020;Jeon & Yamashita, 2014;Juffs & Harrington, 2011;Wen, 2016;Williams, 2012) and meta-analyses (Linck et al, 2014;Shin, 2020) indicate that, overall, working memory has robust, positive links with L2 processing and learning outcomes.…”
Section: Introductionmentioning
confidence: 99%